Extent of knowledge on recommended rice production practices among rice growers in Mayurbhanj district of Odisha - Abhisek, B; Rajeeb, K B; Subrat , K M (Plant Science Today, 2025)
Rice is a vital staple crop that plays a central role in global food security and rural livelihoods, especially in agrarian economies like India. Despite technological advancements in rice cultivation, gaps in farmer awareness and adoption persist. This study assesses the extent of knowledge among 150 rice growers in Mayurbhanj district of Odisha regarding recommended rice production practices, using an ex-post facto survey design and multistage random sampling across five blocks. Findings reveal that the majority of farmers (76 %) had medium-level knowledge, with high familiarity in practices like field preparation, harvesting and post-harvest management, but low awareness in critical areas such as nursery management, seed treatment and pest/disease control. Multiple regression analysis indicated that economic motivation, extension participation, education level and access to information significantly influenced knowledge levels (R² = 0.803). Interestingly, farming experience and innovativeness showed no significant effects. The study underscores the need for targeted extension and capacity-building interventions focusing on foundational and resource-efficient practices. Strengthening institutional support and customising knowledge dissemination strategies can bridge knowledge gaps and enhance sustainable rice productivity in Odisha’s tribal regions.